2022
DOI: 10.7759/cureus.26096
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Increased Residency Applications and How Virtual Interviews Impacted Applicants

Abstract: BackgroundThe number of residency applications submitted by medical students has risen at an alarming rate, causing increased cost of applications and subsequent interview travel. These both contribute to increased cost for medical students. In light of these concerns, specialty governing bodies have proposed ideas to fight these trends including, application limits, interview limits, using a preference signaling system, and continuing virtual interviews. During the Covid-19 pandemic, all residency interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This supports other studies' findings that exclusively virtual interview formats have demonstrated an overall greater number of applications and greater emphasis placed on geographic aspects, including interview offers extended by programs and ultimate match distribution. 10 11 12 13 14 …”
Section: Discussionmentioning
confidence: 99%
“…This supports other studies' findings that exclusively virtual interview formats have demonstrated an overall greater number of applications and greater emphasis placed on geographic aspects, including interview offers extended by programs and ultimate match distribution. 10 11 12 13 14 …”
Section: Discussionmentioning
confidence: 99%